Competency of Elementary School Teachers 84 Sinjai District in Writing Teaching Materials - Abd. Rahman Rahim; Sitti Aida Azis; St. Suwada Rimang (RETORIKA: Jurnal Ilmu Bahasa, 2022)
This study aims to describe the influence between knowledge of writing theory and interest in writing on the ability to write teaching materials for teachers at SD Negeri 84 Sinjai Regency. This research is categorized into the type of quantitative infrensial research. The sample of this research is all teachers of SD Negeri No 84, Sinjai Regency for the 2020/2021 academic year, totaling 24 teachers spread from grade I to grade 6. The data in this study was collected through three techniques, namely test techniques, questionnaires, and documentation. Data analysis was carried out using the percentage technique with the formula: n/Nx100 for the range 10-100 and simple and linear/multiple regression test techniques with computer facilities. The results showed that the level of theoretical knowledge of teaching materials has an average value of 66.10, and is in the medium category. Data analysis of the level of interest in writing teaching materials with an average value of 62.30, and is in the medium category. Data analysis of the level of competence in writing Indonesian language teaching materials with an average value of 63.33, or is in the medium category. Hypothesis testing shows that (1) there is a significant effect between the variables of theoretical knowledge of teaching materials on the competence to write Indonesian teaching materials with a large influence 59.70%, (2) there is a significant influence between the variables of interest in writing teaching materials on the competence to write Indonesian teaching materials with a large influence55.29%. (3) there is a joint significant effect of theoretical knowledge of teaching materials and interest in writing teaching materials on the competence to write Indonesian teaching materials with a large effect of 59.66%.